Community health fairs as experiential learning: a qualitative exploration of benefits and challenges - Rojo, Martha; Wright, Scott; Jin, Jing; Feliciano, Erickson; Love, Margaret; Stevenson, Sharon (BMC medical education, 2025)
Background The shortage of clinical placements and preceptors necessitates innovative approaches to healthcare education. Community health fairs (CHFs) offer a potential solution, but their effectiveness as learning environments is limited. Further, there is lack of recent literature exploring CHFs settings as potential learning environments. This study examined and explored the benefits and challenges of healthcare students and faculty participating in a CHF setting. Methods Using a semi-structured guide developed by the researchers for this study, qualitative conversational interviews were conducted with 14 participants (7 students, 7 faculty) involved in an annual CHF. Prior to the interview, all participants completed a demographic data sheet. All interviews were audio-recorded, transcribed, checked for accuracy, and de-identified, and MAXQDA was used to manage and code the interviews. Two coders analyzed the transcripts, and a third coder served to confirm the qualitative findings, and Clarke and Braun thematic analysis was employed to develop themes. Descriptive statistics were used to describe the sample. Results Seven faculty participated in this study; the age range was 34–64 and years in practice ranged from 7 to 23, four participants were advanced practice nurses (28.6%), two mental health providers (14.3%), and one dental provider (7.1%). The student participants consisted of five dental hygiene students (35.7%) and two nursing students (14.3%). Participants were predominantly female (92.9%), with one male participant (7.1%). The average interview lasted 8 min reflecting the dynamic and fast-paced nature of CHFs. Four major themes emerged from the interviews: (1) Skills development and practical experience, (2) Perspective enhancement, (3) Challenges within the Learning environment, and (4) Recommendations for enhancing health fair settings experiences. Conclusions CHFs can serve as valuable active learning environments that promote clinical skill development and broaden perspectives. To improve CHFs experiences, participants discussed increasing collaborations with other healthcare institutions within the state, making the examination rooms more realistic, and increasing privacy for the patients. Participants also recommended pre-training of healthcare volunteers and incorporating technology for teaching patients. More research is needed to evaluate the utility of CHFs as a learning environment. This is urgent since clinical settings are limited and saturated. Further, researchers should continue doing research in this environment since the literature is scant and dated.